British revenue and judicial policies in India : a case study of Deccan, 1818-1826 - Singh, Meera (New Delhi : Har-Anand Publications, 1994)
Refers to the present Maharashtra.
Includes bibliographical references (p. [226]-229) and index.
Keywords: Chaplin, William; Elphinstone, Mountstuart, -- 1779-1859.; Munro, Thomas, -- Sir, -- 1761-1827.; Maratha (Indic people) -- Politics and government; Revenue -- India -- Deccan -- History; Justice, Administration of -- India -- Deccan -- History; Deccan (India) -- Politics and government